Hubungan antara sistem produksi dan kerjasama kemitraan dengan keberhasilan usahatani tanaman hias Hanjuang (Cordyline fruticosa) di Kecamatan Sukalarang, Kabupaten Sukabumi, Jawa Barat - Mario Gesta Sigarlaki; Euis Dasipah; Karyana KS; Nendah Siti Permana (Fakultas Pertanian Universitas Majalengka, 2022)
This study aims to determine the relationship between the production system and partnership cooperation with the success of Hanjuang (Cordyline fruticosa) ornamental plant farming. The unit of analysis is the Hanjuang Ornamental Plant Farmers in partnership with PT. Noah Han Semesta in Sukalarang District, Sukabumi Regency, West Java Province. The analysis technique used is Pearson correlation analysis and path analysis. The results showed that the performance of Hanjuang ornamental plant farming was quite profitable, with an income of Rp44,957,631,-. The Product planning subsystem; production input subsystem; process subsystem; and control subsystem obtained an achievement level of 80.24% outstanding criteria. Provision of production facilities, Technical guidance, and Marketing of Production Results obtained a level of achievement of 78.95% (good criteria). The following dimensions: productivity; plant quality; and efficiency of farming, obtained a level of achievement of 78.81% (good criteria). Production systems and partnerships have a positive and significant effect on the success of Hanjuang ornamental plant farming. The contribution of the Production System was obtained by 27.27%, and the Partnership and Partnership variable's contribution was 44.24 %.